The Chinese herbal medicine Dai-Zong-Fang promotes browning of white adipocytes in vivo and in vitro by activating PKA pathway to ameliorate obesity - Xu, Jing; Zhang, Li-Wei; Feng, Hui; Tang, Yang; Fu, Shou-Qiang; Liu, Xi-Ming; Zhu, Xiao-Yun (Frontiers in Pharmacology, 2023)
The global prevalence of obesity is rising rapidly. Conversion of white adipose tissue (WAT) into beige adipose tissue with heat-consuming characteristics, i.e., WAT browning, effectively inhibits obesity. Dai-Zong-Fang (DZF), a traditional Chinese medicine formula, has long been used to treat metabolic syndrome and obesity. This study aimed to explore the pharmacological mechanism of DZF against obesity. In vivo, C57BL/6J mice were fed high-fat diets to establish the diet-induced obese (DIO) model. DZF (0.40 g/kg and 0.20 g/kg) and metformin (0.15 g/kg, positive control drug) were used as intervention drugs for six weeks, respectively. Compared with vehicle control group, 0.40 g/kg DZF significantly reduced obesity in DIO mice from body weight, abdomen circumference, Lee’s index, and WAT/body weight (p<0.01 or p<0.001). 0.40 g/kg DZF also significantly reduced fasting blood glucose (FBG), serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) (p<0.01 or p<0.001). The inguinal WAT (iWAT) morphology and mitochondria were browning after DZF intervention. In HE-staining, the lipid droplets became smaller, and the number of mitochondria increased. The mitochondrial structure was remodeled under the electron microscope. The expression of browning markers (UCP1 and PGC-1α) and PKA was elevated in iWAT detected by RT-qPCR (p<0.05 or p<0.001). In vitro, mature 3T3-L1 adipocytes were used as the model. Concentrations of DZF (0.8 mg/mL and 0.4 mg/mL) were selected according to the Cell Counting Kit-8 (CCK8) for 2d. Compared with the control group, 0.8 mg/mL DZF intervention significantly increased the number of mitochondria and expression of UCP1, PGC-1α, PKA, and pCREB (p<0.05 or p<0.01). In contrast, UCP1 and PGC-1α expression were significantly reversed after adding PKA inhibitor H-89 dihydrochloride. The above results suggest that DZF can promote UCP1 expression by activating the PKA pathway, thereby promoting browning of WAT, attenuating obesity, and reducing obesity-related glucose and lipid metabolism abnormalities, indicating that DZF has the potential to be selected as an anti-obesity drug to benefit obese patients.